TRANSFORMASI RUANG LITERASI MENJADI EKOSISTEM PEMBELAJARAN BERMAKNA BAGI SISWA SEKOLAH DASAR - Puji Lestari, Berlian; Siti Aisyah; Neng Intan Juliani; Siti Apsoh; Gilang Mas Ramadhan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the transformation of a school literacy room into a meaningful learning ecosystem that supports the development of fourth-grade students' literacy skills at SD Negeri Sirnagalih. Literacy is a fundamental competence that underlies academic success, yet the mere availability of a physical literacy room does not automatically improve students' reading ability. Using a qualitative descriptive approach, data were collected through observation, in-depth interviews, and documentation involving the principal, the fourth-grade teacher, and fourth-grade students as research subjects. Data were analyzed using the interactive model of Miles and Huberman, comprising data reduction, data display, and conclusion drawing. The findings indicate that the literacy room evolves into a meaningful learning ecosystem when several interrelated components function synergistically, namely varied and age-appropriate reading materials, a structured literacy program, a comfortable physical setting, teacher facilitation, peer interaction, family support, and consistent evaluation. Within this ecosystem, students demonstrated progressive improvement in reading fluency, reading comprehension, the ability to identify main ideas, retelling skills, and writing simple summaries, along with a stronger reading habit and greater confidence in communicating ideas. The study concludes that a literacy room reaches its optimal function not as a static facility but as a living ecosystem integrating space, program, and human interaction that jointly nurtures meaningful and sustainable literacy learning among elementary school students.